Between Future and Past: An Exercise in Political Ecology - Robinson, Benjamin Lewis (HannahArendt.net, 2018)
This paper on Arendt and the Anthropocene was presented at the conference, “Post-Truth and Politics,” hosted and organized by the Berlin ICI Institute for Cultural Inquiry in collaboration with the Hannah Arendt Center at Bard College and Bard College Berlin on April 29, 2017. The conference departed from Arendt’s 1967 essay, “Truth and Politics,” which responded to historical exigencies that seem, some fifty years later, to resonate with those presented by the advent of the so-called “post-truth society.”